Strategi Peningkatan Kreativitas Anak dan Stimulasi Speech Delay Melalui Media Loose Part di PAUD - Yenny Wardati Arifah; Togar Siagian; Siti Rohmah; Sigit Purnama (Universitas Islam Tribakti Lirboyo Kediri, 2024)
In the era of globalization, creativity is becoming increasingly important, because it is needed to face increasingly rapid challenges and changes. To increase creativity in early childhood, the right strategy is needed, one of which is using loose part media. At PAUD Fullday Aisyiyah Kasihan uses loose parts as a strategy to increase children's creativity. So the aim of this research is to look at strategies for increasing children's creativity through loose part media at PAUD Fullday Aisyiyah Kasihan. This research uses descriptive qualitative research. The research subject is the teacher. The place of research was carried out at the Kasihan Integrated Aisyiyah PAUD, Bantul, Yogyakarta. The validity tester in this research uses credibility with triangulation, namely technical triangulation. Analyzing data from the field through interview, observation, and documentation techniques. The data analysis technique that will be used in the research is Miles and Huberman's data analysis technique, namely data reduction, data display, and conclusions. The results of the research show that there are 6 strategies used by teachers to increase children's creativity by using loose part media, namely; 1) giving children freedom to imagine and be creative; 2) providing appropriate direction and supervision by the teacher; 3) getting used to playing activities with loose part media; 4) use of interrogative sentences and provocation sentences to support creativity; 5) increasing vocabulary, articulating word pronunciation and strengthening children's oral speech; 6) assessment of activity results and reflection on learning.